The Relationship between Adolescent Pregnancy and Stunting among Toddlers Aged 12-36 Months in Bogor District, Indonesia (Indian Journal of Public Health Research & Development, 2020)
Background: Stunting is a serious problem that needs to be handled both in Indonesia and globally.Approximately 151 million, or 22.2%, of toddlers in the world are currently stunted. The purpose of thisstudy is to assess the relationship between adolescent pregnancy and stunting in toddlers aged 12-36 monthsin Bogor District, Indonesia.Method: A cross-sectional study design was employed, with primary data from a total sample of 500toddlers in the District. Stunting status was assessed based on the height-for-age indicator
Keywords: Stunting, 12–36 months, Toddlers, Adolescent Pregnancy, Bogor District Indonesia